Robust parametric optimization systems stabilization of ground moving objects - Сущенко, О.А. (Proceedings of National Aviation University (archive), 2008)
Features of the ground vehicle robust stabilization system parametric synthesis are analysed. Approaches to its solution are suggested. The simulation results are represented.